The Survey of Food Consumption Among Traders with Hypertension at Bantul Traditional Market - Ririn Wahyu Hidayati (International Journal of Health Science and Technology, 2020)
Hypertension is a non-communicable disease which ranks in the top 3. Untreated hypertension will have an impact on increasing the incidence of stroke and coronary heart disease. The prevalence of hypertension in Indonesia is 25, 8%, while the incidenceof hypertension in Special Region of Yogyakarta is 25,7%. In Indonesia in 2017, 77% of people with a history of hypertension had a stroke. Therefore, in 2025 it is projected that 29% of the world's population or as many as 1.56 billion adults will experience hypertension. This is influenced by several factors, one of which is an unhealthy lifestyle. Efforts that have been made by Indonesia in the prevention and control of hypertension with "CERDIK" behavior. This study aims to determine the types of food consumed by traditional market traders in Bantul who have hypertension. The study used a simple quantitative descriptive design with cross sectional approach. The population in this study were 87 traders. Samples were taken by purposive sampling method, namely all traders who have hypertension and are willing to be respondents as many as 50 traders. This research is expected to increase public awareness independently and research data can be used as basic health data for traders and follow-up for health workers for appropriate hypertension management in the community.